Analysis of initial crack path in fretting fatigue - J. Vazquez; S. Astorga; C. Navarro; J. Dominguez (Fracture and Structural Integrity)
The initial crack path is analysed in a fretting fatigue test with cylindrical contact, where there is a stress gradient and a multiaxial and non-proportional stress state. For this, a cylindrical pad is pressed, with a constant normal load, N, against a dog-bone type fatigue test specimen. Then, the test specimen is subjected to a cyclic axial stress, ?. Due to the cyclical axial stress, the assembly used and the friction between the contact pair, a tangential cyclic load Q is generated. In these tests, both components are made of Al7075-T651 alloy. The crack initiation path along the fracture surface is optically measured using a focus variation technique. The contact stress/strain fields obtained analytically, in junction with the Fatemi-Socie (FS) and Smith-Watson- Topper (SWT) multiaxial fatigue parameters, allow us to determine the controlling parameters of the crack initiation process observed in the tests and to estimate the crack path during the early stage of the crack growth.